FORMULA JELLY DRINK CINCAU HIJAU, PANDAN WANGI DAN KAYU MANIS UNTUK MENURUNKAN KADAR GULA DARAH PENDERITA DIABETES MELITUS - Zaenal Amirudin; Rosmiati Saleh; Afiyah Sri Harnany (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2019)
Background: Treatment of diabetes mellitus has been in the form of insulin injections and oral antidiabetic drugs. Green grass jelly leaves, fragrant pandanus and cinnamon are herbal plants that can be developed into jelly drinks as a therapeutic-based functional food to prevent the risk of diabetes mellitus. The purpose of this study was to make jelly drink made from green grass jelly, fragrant pandanus and cinnamon and its effect on blood glucose levels. Methods: The study began with a hedonic organoletic test to determine the selected jelly drink formula for 20 panelists. Followed by the experimental method of Pretest-Postest Group Design. Results: organoleptic test in the most preferred product with a comparison of green cincau leaves: fragrant pandan leaves (90: 10 / v: v) plus 0.5% cinnamon filtrate and 0.5 gram stevia sugar. The average blood glucose level in the control gro up decreased on days 14 and 21. The ANOVA test results showed no significant difference in the decrease in blood glucose levels between groups (value 0.124 > 0.05). the ANOVA test result level in the intervention group experienced a decrease in days 7, 14 and 21. The ANOVA test results showed that there were significant differences between groups ((value 0.001